Exceptional damping of CFRPs: Unveiling the impact of carbon fiber surface treatments - Feng, Jigang; Gao, Chuang; Safaei, Babak; Qin, Zhaoye; Wu, Haihong; Chu, Fulei; Scarpa, Fabrizio (Elsevier Sci Ltd, 2025)
A significant body of research has concentrated on augmenting the interfacial slippage between carbon fiber (CF) fabrics and resin to improve the damping properties of CF reinforced plastics (CFRPs). However, a critical but commonly overlooked issue lies in the fact that a higher number of mutual slippage interfaces may lead to potential debonding at the interface. This, in turn, not only influences mechanical properties but also escalates the risk of structural damage. In this study, three distinct modification methods are proposed to alter the surface characteristics of CFs, achieving simultaneous enhancement of the damping and mechanical properties of CFRPs. Specifically, the polymerization of dopamine on the CF surface results in CFRPs with a loss factor of 0.227 at 1 Hz, which is 180 % higher than the 0.081 of referenced CFRP. Additionally, using this modification method, the tensile modulus and strength of the CFRP are increased by about 11.3 % and 6.7 %, respectively. More importantly, the subtle relationships within the CFRPs interface are explored through the different surface modification methods. The interactions between surface wettability, specific surface area, roughness, and interfacial chemical bonding on the mechanical and damping properties are redefined and elucidated. This study demonstrates that surface modification can simultaneously enhance both the damping and mechanical properties of CFRPs, and a satisfactory balance of multiple enhancement effects can be achieved by adjusting the surface modification factors.
Keywords: CFRPs; Damping properties; Interface boding strength; Polydopamine; Polyethyleneimine